Comparative Study of Parenteral Penicillin G vs. Amoxicillin-Clavulanate for the Treatment of Dentoalveolar Abscess in Hospitalized Children - Adler, Amos; Gadot de-Vries, Irit; Amir, Jacob; Ashkenazi-Hoffnung, Liat (Frontiers in Pediatrics, 2021)
Objectives: To compare the clinical efficacy and the safety profiles of parenteral penicillin vs. amoxicillin-clavulanate for the treatment of dentoalveolar abscess (DA) in hospitalized pediatric patients. Methods: A retrospective cohort study that was conducted at the Schneider Children's Medical Center in Israel. Results: Seventy-one patients that were included, 25 received parenteral penicillin and 46 amoxicillin-clavulanate. There were no significant differences in the baseline clinical features except for higher rate of females in the amoxicillin-clavulanate group. Patients that were treated with penicillin had shorter duration of fever, swelling and total length-of-stay (4.16 vs. 5 days in the penicillin vs. amoxicillin-clavulanate groups, respectively, p=0.007) and lower need for surgical intervention. Side effect were minor in both groups. In multivariate analysis, antimicrobial regimen was the only significant factor related with the total length-of-stay (p<0.001). Conclusions: In pediatric patients hospitalized for DA, parenteral penicillin was associated with better outcome compared with amoxicillin-clavulanate.